Detective Comics : 80 years of Batman (DC Comics, 2018)
Join us in a celebration of Detective Comics' amazing eight-decade run and Batman's 80 years, with reflections on Detective Comics by Cory Doctorow, Neil Gaiman, Glen David Gold, Senator Patrick Leahy, Denny O'Neil, Anthony Tollin, police chief Shelley Zimmerman and Paul Levitz. This special collector's edition also features the very first Batman story; the debuts of classic sidekicks and allies like Robin, Batgirl, Batwoman and even Bat-Mite; and the first stories of archvillains Two-Face, the Riddler and Man-Bat.